STUDY OF THE MAIN PARAMETERS OF THE EXPLOSIVE EFFECT FOR PRACTICAL CALCULATIONS OF THE STRENGTH AND STABILITY OF TUNNEL STRUCTURES - Tiutkin, A. L. (Science and Transport Progress, 2006)
The article presents the results of studying the basic parameters of explosive influence for practical calculations of durability and stability of tunnel constructions. The obtained dependences of basic parameters are functions and have an applied nature.